Developing the capacity of farmers to understand and apply seasonal climate forecasts through collaborative learning processes. Issue 4 (7th August 2016) - Cliffe, Neil; Stone, Roger; Coutts, Jeff; Reardon-Smith, Kathryn; Mushtaq, Shahbaz
ABSTRACT: Purpose : This paper documents and evaluates collaborative learning processes aimed at developing farmer's knowledge, skills and aspirations to use seasonal climate forecasting (SCF). Methodology : Thirteen workshops conducted in 2012 engaged over 200 stakeholders across Australian sugar production regions. Workshop design promoted participant interaction, stimulated discussion, collected farmer experience of regional climate variability, improved understanding of climate drivers and increased participant skill in interpreting SCF linked to management decisions. Post-workshop surveys collected quantitative and qualitative data for statistical analysis and manual thematic coding. Findings : Over 68% of participants identified improved decision-making and risk reduction as the main benefits of using SCF products. High median self-evaluation ratings for gains in skills, knowledge and understanding of climate forecasts and perceived benefits in using climate forecasts in on-farm decision-making were found across stakeholder groups. No significant differences in self-evaluation rating gains were found between farmers, extension officers and millers, suggesting extension officers are less than optimally informed and skilled to support farmers in understanding and applying SCF. Practical Implications : Developing the capacity of extension officers to understand and interpret SCF may increase adoption of improved climate risk management in farmer networks. Theoretical implications : Collaborative learning activities in the agriculture sector, designed using experiential learning principles and evaluated using a logical framework, provide a robust model for improving the capacity of farmers to manage climate risk. Originality/Value : This paper contributes an example of evaluation of collaborative learning in facilitated agriculture climate risk workshops and discusses the value of learning through small group discussion.